PENGARUH PEMUASAAN DAN PENAMBAHAN KUNYIT (CURCUMA LONGA) DALAM PAKAN TERHADAP PERSENTASE ORGAN PENCERNAAN BROILER - Hardianti Hardianti; Siti Nursayang; Putra Astaman (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2023)
This study aims to determine the effect of fasting and the addition of turmeric powder in feed on the percentage of organs digestion in broilers. Strain used in this study that is Cobb 707. There were 100 chicken used in the study. Each animal treachment group of each replications was placed in a floor pen (1.0 m x 1.0 m x 1.0 m). The research was arranged on completely randomized design (CRD) 4 treatments with 5 replication; P1= No fasting – no addition of turmeric powder; P2: no fasting - 1% turmeric powder; P3: daily fasting (12 hours) - no addition turmeric powder; P4: daily fasting (12 hours) - 1% turmeric powder. Daily fasting programs and addition of turmeric powder in feed were started at the age of 15 days. The fasting program was betwen 6.00 am to 6.00 pm. The feed used was commercial feed in the granules form (1-14 days) and in the form flour form (15-35 days). Drinking water was provided unrestrictedly. The results show that the daily fasting and addition of turmeric powder did significantly (P<0,05) affect the gizzard percentage, colon percentage, small intestine percentage and no significant (P>0.05) effect the percentage of the pancreas.Keywords: Broiler, proportion of internal organs digestion, fasting, turmeric flour